2020
DOI: 10.1007/s00259-020-04842-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of CNS microglial activation/macrophage infiltration with combined [18F]DPA-714-PET and SPIO-MRI in a mouse model of relapsing remitting experimental autoimmune encephalomyelitis

Abstract: Purpose To evaluate the feasibility and sensitivity of multimodality PET/CT and MRI imaging for non-invasive characterization of brain microglial/macrophage activation occurring during the acute phase in a mouse model of relapsing remitting multiple sclerosis (RR-MS) using [ 18 F]DPA-714, a selective radioligand for the 18-kDa translocator protein (TSPO), superparamagnetic iron oxide particles (SPIO), and ex vivo immunohistochemistry. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…The in vivo PET data were confirmed by IHC, demonstrating that TSPO expression was limited to microglial cells while astrocytes were TSPO negative. Additionally, Nack et al [190] reported that TSPO + cells were microglia following cuprizone treatment and that supplementing Cuprizone with MOG 35-55 peptide immunization drove the recruitment of TSPO + monocytes in the lesion contributing to the overall PET signal on top of resident activated microglia; these results are in agreement with a more recent study with [ 18 F]DPA714 [194]. Interestingly, Zinnhardt et al [193] showed using [ 18 F]DPA714 that during demyelination TSPO + cells consisted only of microglia, while during remyelination, astrocytes also became TSPO + .…”
Section: Models Of Multiple Sclerosissupporting
confidence: 81%
See 1 more Smart Citation
“…The in vivo PET data were confirmed by IHC, demonstrating that TSPO expression was limited to microglial cells while astrocytes were TSPO negative. Additionally, Nack et al [190] reported that TSPO + cells were microglia following cuprizone treatment and that supplementing Cuprizone with MOG 35-55 peptide immunization drove the recruitment of TSPO + monocytes in the lesion contributing to the overall PET signal on top of resident activated microglia; these results are in agreement with a more recent study with [ 18 F]DPA714 [194]. Interestingly, Zinnhardt et al [193] showed using [ 18 F]DPA714 that during demyelination TSPO + cells consisted only of microglia, while during remyelination, astrocytes also became TSPO + .…”
Section: Models Of Multiple Sclerosissupporting
confidence: 81%
“…Various studies investigated the neuroinflammatory profile of different models of MS (EAE or WM lesion) using [ 18 F]PBR111 [188], [ 18 F]VC701 [189], [ 18 F]GE-180 [190][191][192] or [ 18 F]DPA-714 [193,194] PET tracers. Overall, TSPO imaging studies in MS models consistently reported a moderate to large increase in TSPO tracer uptake in the affected brain regions.…”
Section: Models Of Multiple Sclerosismentioning
confidence: 99%
“…Ultimately, correlative [18F]DPA-714-PET and MRI-USPIOs together with confocal imaging allowed to investigate microglia/macrophage properties in an experimental autoimmune encephalomyelitis mouse model of multiple sclerosis. This work showed that microglia/macrophages upregulate TSPO and IBA1 in the demyelinating regions during acute phases, suggesting their dysfunction as a contributing factor to the inflammation seen in multiple sclerosis (Coda et al, 2020).…”
Section: Mrimentioning
confidence: 66%
“…In principle, VBA techniques can be formally applied, in a similar way, to both functional imaging and dosimetric datasets; however, there is a substantial difference between the two fields that warrants caution during result interpretation. Indeed, in functional imaging, VBA can identify the metabolic patterns that depend only on the investigated pathophysiology, at least as long as the chosen image contrast, which is usually given by the contrast medium in nuclear medicine and by the pulse sequence in MRI, allows for an effective representation of the underlying functional mechanisms [33,34]. In radiation oncology, on the contrary, VBA can identify those dose patterns that not only depend on the regional radiosensitivity, but are also within the reach of the intrinsic heterogeneity of the dose distributions included in the analyzed dataset.…”
Section: Discussionmentioning
confidence: 99%